Per capita versus adult-equivalent estimates of calorie availability in household budget surveys Estimativa domiciliar da disponibilidade calórica per capita versus adulto-equivalente em pesquisa de orçamento familiar - Rafael Moreira Claro; Renata Bertazzi Levy; Daniel Henrique Bandoni; Lenise Mondini (Cadernos de Saúde Pública, 2010)
This study aims to estimate an adult-equivalent scale for calorie requirements and to determine the differences between adult-equivalent and per capita measurements of calorie availability in the Brazilian population. The study used data from the 2002-2003 Brazilian Household Budget Survey. The calorie requirement for a reference adult individual was based on the mean requirements for adult males and females (2,550kcal/day). The conversion factors were defined as the ratios between the calorie requirements for each age group and gender and that of the reference adult. The adult-equivalent calorie availability levels were higher than the per capita levels, with the largest differences in rural and low-income households. Differences in household calorie availability varied from 22kcal/day (households with adults and an adolescent) to 428kcal/day (households with elderly individuals), thus showing that per capital measurements can underestimate the real calorie availability, since they overlook differences in household composition. Objetivou-se estimar uma escala adulto-equivalente de necessidade energética e determinar as diferenças entre medidas adulto-equivalente e per capita para disponibilidade energética da população brasileira. Utilizaram-se dados da Pesquisa de Orçamentos Familiares de 2002/2003. A necessidade energética de um indivíduo adulto de referência baseou-se na média das necessidades de homens e mulheres adultos (2.550kcal/dia). Os fatores de conversão foram definidos como a razão entre a necessidade energética de cada grupo de idade e sexo e aquela do adulto de referência. Os valores de disponibilidade de energia adulto-equivalente foram superiores aos per capita, sendo as maiores diferenças nos domicílios da área rural e de menor renda. As diferenças na disponibilidade energética domiciliar variavam entre 22kcal/dia (domicílio contendo adultos e adolescente) e 428kcal/dia (domicílio onde residem idosos), demonstrando que medidas per capita podem subestimar a disponibilidade energética real, uma vez que ignoram diferenças na composição dos domicílios.